Pola Kepekaan Antibiotik Fosfomycin terhadap Bakteri Patogen Penyebab Infeksi Saluran Kemih Pasien Dewasa di Rumah Sakit X pada Periode Tahun 2023 - Ebat, Aelred Parleso; Gunardi, Wani Devita; Pasaribu, Donna Mesina Rosadini (Jurnal MedScientiae, 2025)
Urinary Tract Infection (UTI) is an infection of the urinary tract structure which is generally caused by Escherichia coli with a prevalence of 5-15% with an estimated 180 thousand cases per year in Indonesia, making it the most common disease today. This is further exacerbated by increasing resistance to conventional antibiotics such as amoxicillin, cephalosporins, and fluoroquinolones which makes the selection of UTI therapy increasingly difficult. This study aims to determine the sensitivity of fosfomycin antibiotics to pathogens that cause UTI in adult patients at Hospital X in the period 2023. This study used an observational method, with a retrospective descriptive approach by collecting and analyzing secondary data from the microbiology laboratory of Hospital X. The sampling technique used total sampling with a sample size of 51. Using univariate analysis, it was found that women and the elderly group had a fairly high risk of UTI, with E. coli being the most common etiology (51.8%). Fosfomycin was shown to have a high level of sensitivity (96.55%) to E. coli. Therefore, it can be concluded that fosfomycin has a high level of sensitivity to pathogens that cause UTI infections in adult patients at Hospital X in 2023. This study will be more accurate if the number of samples can be increased again.